Etude de l’activité insecticide de l’huile essentielle de Juniperus oxycedrus vis-à-vis de Tuta absoluta - AZZOUZ, Redouane (My University, 2020)
The tomato leafminer, Tuta absoluta (Meyrick), is a major pest of tomatoes in Algeria. Since its spread, chemical control was the main method of control. However, reduced effectiveness of some of the recommended insecticides has been observed. This study aims to propose alternative solutions based on the use of natural products "bioinsecticide" to fight against the tomato leafminer, Tuta absoluta (Meyrick), which is considered a serious threat to tomato production in Algeria and worldwide.To achieve this objective, we evaluated the toxicity of the essential oil of Juniperus oxycedrus L. against larvae of Tuta absoluta. Bioassays were performed in vitroin petri dishes 9 cm in diameter. The determination the lethal doses 50 and 90 (LD50/LD90) of this essential oil has been made. The values of LD50 and LD90 are respectively 3.09and8.19%calculated after eight days of exposure confirms the high degree of toxicity of the essential oil of Juniperus oxycedrus L. against the larvae of Tuta absoluta. Essential oils role in the fight against tomato leafminer is discussed.
Keywords: Tomato; Tuta absoluta (Meyrick); Bioinsecticides; Juniperus oxycedrus L.; Essential oils.